Guilty by association: How group-based (collective) guilt arises in the brain - Li, Zhiai; Yu, Hongbo; Zhou, Yongdi; Kalenscher, Tobias; Zhou, Xiaolin (NeuroImage (Orlando, Fla.), 2020)
People do not only feel guilty for transgressions that they are causally responsible for (i.e., personal guilt); they also feel guilty for transgressions committed by those they identify as in-group members (i.e., collective or group-based guilt). Decades of research using scenario-based imagination tasks and self-reported measures has shown that when reminded of transgressions committed by in-group members, people express guilt and are willing to make amends, even when they are not causally responsible for the transgressions. However, it remains elusive whether people genuinely experience guilt or simply display remorseful gestures deemed appropriate in those contexts. To resolve this puzzle, it is critical to closely examine the neurocognitive basis of group-based guilt and its relationship with personal guilt, a goal that self-reported measures alone cannot satisfactorily achieve. Here, we combined functional MRI with an interaction-based minimal group paradigm in which participants either directly caused harm to a group of victims (i.e., personal guilt), or observed in-group members cause harm to the victims (i.e., group-based guilt). In three experiments (N ​= ​90), we demonstrated and replicated that the perceived responsibility one shared with in-group members in transgression predicted both behavioral and neural manifestations of group-based guilt. Multivariate pattern analysis (MVPA) of the functional MRI data showed that group-based guilt recruited patterns of neural responses in anterior middle cingulate cortex that resembled personal guilt. These results have broadened our understanding of how group membership is integrated into the neurocognitive processes underlying social emotions. •An interaction-based minimal group paradigm was used to elicit group-based and personal guilt in laboratory settings.•Group-based guilt motivated reparation for transgression committed by in-group members.•Shared responsibility with in-group members in a transgression explained group-based guilt and reparation.•Group-based guilt was associated with activations in anterior middle cingulate cortex and right anterior insula.•Group-based guilt and personal guilt shared a similar neurocognitive representation.